Impact of perinatal mental health education on student midwives' knowledge, skills and attitudes: A pre/post evaluation of a module of study. (January 2016) - Higgins, Agnes; Carroll, Margaret; Sharek, Danika
Summary: Background: Whilst midwives are well-placed to identify and address the mental health need of women in their care, many report lacking the ability to do so. Therefore, they ignore or brush aside women's mental health needs. To improve midwives' competency in this area, the first authors developed and delivered a module on perinatal mental health issues within their university. The module aimed to improve knowledge, skills, and attitudes in relation to working with women about mental health issues. In 2012, a post-survey evaluation of the module demonstrated positive findings; following a number of revisions to the module, this more robust pre/post evaluation was conducted. Objectives: The objective of this study was to examine the impact of the perinatal mental health module on student midwives' knowledge, skills, and attitudes in addressing mental health issues with women. Design Pre-module and Post-module Surveys were Used. Participants: Participants were students undertaking a 4-year undergraduate direct entry midwifery degree programme in Ireland. The pre-survey had 28 participants, the post-survey had 26 participants, and there were 25 matched pairs. Methods: The data were analysed using SPSS Version 21.0. Descriptive, frequencies and paired sample t-tests were calculated. Qualitative data were analysed thematically. Results: Comparison of the pre and post measures, based on paired samples t-tests, showed that the programme statistically increased participants' knowledge and skills. Whilst students' self-reported attitudes towards women and mental health issues were already quite positive, they reported even more positive attitudes following the course. Written feedback provided by students also supported these positive findings. Conclusion: This evaluation provides evidence that a module on perinatal mental health is effective at improving the self-reported knowledge, skills, and attitudes of student midwives towards women with mental health issues. It is recommended that educators consider the opportunity of including a similar module in their curriculum. Highlights: The study examined the impact of a perinatal mental health module on student midwives' knowledge, skills and attitudes. Students reported high satisfaction rates with module. Statistically significant differences for knowledge and skill were found using a repeated measure survey design. Educators consider including a similar module in preregistration midwifery curriculum.